2022
DOI: 10.3389/fnmol.2022.994270
|View full text |Cite
|
Sign up to set email alerts
|

Genetically proxied gut microbiota, gut metabolites with risk of epilepsy and the subtypes: A bi-directional Mendelian randomization study

Abstract: BackgroundAn increasing number of observational studies have revealed an association among the gut microbiota, gut metabolites, and epilepsy. However, this association is easily influenced by confounders such as diet, and the causality of this association remains obscure.MethodsAiming to explore the causal relationship and ascertain specific gut microbe taxa for epilepsy, we conducted a bi-directional Mendelian randomization (MR) study based on the genome-wide association study (GWAS) data of epilepsy from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…We followed three core assumptions to identify the IVs we needed. First, setting a statistical significance threshold of 1 × 10 −5 [ 24 ], screening out genetic variant SNPs that were strongly associated with the microbe but not directly associated with URTIs and LITIs, and excluding minor allele frequencies (MAFs) with a threshold of 0.01. We assessed the power of the instrumental variables using the F value [ 25 ], F = R 2 × (N – 1 − i)/(1 − R 2 ) × i , and IVs with an F less than 10 were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…We followed three core assumptions to identify the IVs we needed. First, setting a statistical significance threshold of 1 × 10 −5 [ 24 ], screening out genetic variant SNPs that were strongly associated with the microbe but not directly associated with URTIs and LITIs, and excluding minor allele frequencies (MAFs) with a threshold of 0.01. We assessed the power of the instrumental variables using the F value [ 25 ], F = R 2 × (N – 1 − i)/(1 − R 2 ) × i , and IVs with an F less than 10 were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In the MR study, single nucleotide polymorphisms (SNPs) are regarded as an instrumental variables (IVs) to estimate the causal relationship between exposure and outcome (19). Previous studies have found the causal relationship between human blood metabolites, gut microbiota, circulating lipids, psychiatric disorders and epilepsy (20)(21)(22)(23)(24). In recent years, an increasing number of studies have examined the association between plasma lipidome and epilepsy, yet no research has explored this relationship at the genetic level.…”
Section: Introductionmentioning
confidence: 99%
“…The Mendelian randomization (MR) strategy is a technique used to investigate the possible causal link between exposure and outcome using instrumental variables (IVs). MR has been used to show that gut microbiota is correlated with a variety of diseases 17–20 . However, MR has not been employed to investigate the causal links between gut microbiota and COVID‐19 at present.…”
Section: Introductionmentioning
confidence: 99%
“…MR has been used to show that gut microbiota is correlated with a variety of diseases. [17][18][19][20] However, MR has not been employed to investigate the causal links between gut microbiota and COVID-19 at present. In this work, the GWAS data sets from an earlier study 21 were used to find the underlying linkages between gut microbiota and COVID-19 using a MR analysis.…”
mentioning
confidence: 99%